TOXIC DIGITAL INFLUENCE: BUILDING ARTIFICIAL AUTHORITY THROUGH FAKE NEWS ON INSTAGRAM (Editora Impacto Científico, 2025)
The rise of Instagram as an ecosystem of influence has transformed informational dynamics and expanded the ability of digital actors to build artificial authority. This article analyzes how profiles—from micro-influencers to large creators—use strategies of disinformation, emotional manipulation, and aesthetic credibility to fabricate legitimacy among their followers. The research discusses how the platform's algorithmic logic favors polarizing, sensationalist, or partially false content, accelerating its viral spread and reinforcing users' cognitive biases. Based on a theoretical review and critical analysis of communication patterns, it demonstrates that artificial authority has direct impacts on opinion formation, individual decision-making, and digital markets, influencing everything from purchasing behavior to political perceptions. By investigating this illusory power, the study points to social, economic, and psychological risks, as well as proposing ways to mitigate them, media literacy, and improve the algorithmic guidelines of the platforms.DOI: https://doi.org/10.56238/edimpacto2025.090-072